A novel paraffin/expanded perlite composite phase change material for prevention of PCM leakage in cementitious composites. (1st November 2015) - Ramakrishnan, Sayanthan; Sanjayan, Jay; Wang, Xiaoming; Alam, Morshed; Wilson, John
Highlights: Paraffin/hydrophobic coated expanded perlite PCM composite was developed. PCM leakage in the thermal energy storage system was prevented. Microstructural and mechanical properties of PCM integrated concrete were investigated. Thermal performance of PCM integrated concrete panel was studied. Abstract: In this study, a novel thermal energy storage composite was developed by impregnating paraffin into hydrophobic coated expanded perlite (EPO) granules. A paraffin/uncoated expanded perlite (EPW) phase change composite was also prepared to study and compare the stability when integrated into cementitious composites. Paraffin/EPW, containing 35% by weight of paraffin, showed significant leakage of phase change material (PCM) during integration into concrete. However, no PCM leakage was observed for novel paraffin/EPO containing 50% by weight of paraffin in the composite. Microstructural and mechanical properties were studied for the compatibility of hydrophobic coated PCM composite in concrete. The thermal behaviour of a concrete panel incorporating PCM was studied and compared with the reference panel. The results revealed that incorporation of the developed PCM composite into concrete significantly improved the thermal inertia and thermal energy storage.